The Effect of Body Mass Index on Bleeding After on Pump Coronary Artery Bypass Grafting - Siddiqeh, Musfireh; Khan, Imran; Fayyaz, Fakher-e-; Dawood, Muhammad Awais; Hasan Kirmani, Syed Muzaffar; Khurshid, Hannah; Javaid, Rehana (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the relationship of body mass index (BMI) and postoperative bleeding in patients undergoing isolated coronary artery bypass grafting (CABG) using cardiopulmonary bypass (CPB).Study Design: Analytical cross sectional studyPlace and Duration of Study: Cardiothoracic services, Almana General Hospital, Al Khobar, Saudi Arabia, from Oct 2019 to Oct 2021. Methodology: Two hundred and twenty (220) consecutive patients who underwent CABG using cardiopulmonary bypass were included in the study. Patients who had additional procedures, those who were operated in emergency and those with significant comorbidities like hepatic and liver dysfunction were excluded from the final analysis. Patients were divided into three groups according to their BMI, healthy weight (BMI 18.5 to